PEMODELAN ENDAPAN BATUBARA KABUPATEN BULUNGAN PROVINSI KALIMANTAN UTARA (Jurnal Geomine, 2016)
Modelling of the coal deposit is an activity that aims to identify the seams and the thickness of coal in order to provide the efficiency and accuracy at the mine site. This research aimed to determine the continuity of the coal seam located in the mine site. The method used in this research was a correlation using the drill log data (seam, thickness, depth). The results of the cross section A-A’ from the south to the north with average thickness of 15,32m. The results of the cross section B-B’ from the south to the north with average thickness of 8,08m. The results of the cross section C-C’ from the south to the north with average thickness of 8m. The results of the cross section D-D’ from the south to the north with average thickness of 19,09m. The results of the cross section E-E’ from the south to the north with average thickness of 11,95m. The results of the cross section F-F’ from the south to the north with average thickness of 13,25m. Of the correlation results of the six cross sections, the conclusion is that the continuity of the coal seam from the south to the north is relatively thicker than from other directions.